Pendampingan UMKM Katering “Masak-masak.id” di Kegiatan Festival “Singosari Tempoe Doeloe” Sebagai Strategi Branding - Finahari, Nurida; Rubiono, Gatut (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Catering MSMEs need marketing efforts to introduce their business and products to the consumer community. One form of marketing is direct marketing at festivals or exhibitions. This community service activity is carried out as a form of assistance for catering businesses in festival activities as a branding strategy. The strategic location of partner production sites at the festival activity location is used as a marketing medium. Activities are carried out by planning the layout of partner stands and daily evaluations during the three-day festival activities. Changes were made so that the visiting public would be more interested in activity partners. The results of the activity show that changes in the appearance of the booth as a result of evaluation on the first day of the festival can increase visitor interest towards partners.